Neuroprotection after transient middle cerebral artery occlusion in male rats using kojic acid nanostructured lipid carriers: A behavioral, biochemical, and histological study on hippocampal CA1 region - Mobina Gheibi; Erfan Ghadirzadeh; Javid Tebyani; Seyedeh Mohadeseh Moyaedi; Khadijeh Khezri; Majid Saeedi; Ali Siahposht‐Khachaki; Narges Karimi; Melika Pourhossein; Shiva Shadi; Sasan Shafiei; Atena Sharifi‐Razavi (Animal Models and Experimental Medicine, 2026)
Abstract Background Ischemic stroke triggers neuroinflammation and oxidative stress, leading to neuronal damage. Kojic acid (KA) has exhibited neuroprotective properties in other neurological pathologies but suffers from poor bioavailability. This study investigated whether KA encapsulated in nanostructured lipid carriers (KA‐NLC) exerts protective effects against cerebral ischemia. Methods Eighty adult male Wistar rats were subjected to transient middle cerebral artery occlusion (MCAO) or control procedures and allocated into 10 experimental groups ( n = 8 per group): intact, sham, MCAO, vehicle, three free‐KA solution groups (10, 20, and 40 mg/kg), and three KA‐NLC groups (1, 2, and 4 mg/kg). Functional outcomes were assessed using neurological scoring and Rota‐Rod, Morris water maze, and shuttle box tests. Brain water content, hippocampal histology, and cerebrospinal fluid cytokine levels (interleukin‐10 [IL‐10], tumor necrosis factor‐α [TNF‐α]) were also evaluated. Results Treatment with low and medium doses of KA‐NLC and medium and high doses of free KA significantly reduced brain edema and improved neurological scores, motor coordination, and memory performance compared to the MCAO group. These functional improvements were associated with a significant increase in anti‐inflammatory IL‐10 and a modulation of TNF‐α. Histological examination confirmed neuroprotection, with KA‐NLC preserving hippocampal CA1 neural integrity. The high dose of KA‐NLC and the low dose of free KA however were ineffective. Conclusions Nanoformulated KA confers significant neuroprotection against ischemic stroke by reducing edema, modulating inflammation, and preserving neuronal integrity, presenting a promising therapeutic strategy.